PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. REKSO NASIONAL FOOD CABANG EDUTOWN BSD - Setiawan, Ahmad; Aprilliani, Siti (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of the work environment and work discipline on employee performance at PT. Rekso Nasional Food Cabang Edutown BSD either partially or simultaneously. The method used is the Quantitative Associative method. The population in this study were all employees of PT. Rekso Nasional Food Cabang Edutown BSD. The sampling technique used was the saturated sample method with a sample of 62 respondents. The data analysis method uses simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination, partial t test and F test. The results of this research show that there is a positive and significant influence of the work environment on employee performance at PT. Rekso Nasional Food Cabang Edutown BSD, this can be proven from the simple linear regression equation Y = 16.016+0.400X1. The correlation value is 0.662 (strong). The coefficient of determination value is 43.8%. The tcount value is 6.842 > ttable 2.000 with a significance of 0.000 < 0.05. There is a positive and significant influence of Work Discipline on employee performance at PT. Rekso Nasional Food Cabang Edutown BSD, this can be proven from the simple linear regression equation Y=14.083+0.440X2. The correlation value is 0.691 (strong). The coefficient of determination value is 47.7%. The t value is 7.403 > t table 1.988 with a significance of 0.000 < 0.05. Simultaneously there is a positive and significant influence of the Work Environment and Work Discipline on employee performance at PT. Rekso Nasional Food Cabang Edutown BSD, this can be proven from the multiple linear regression equation Y=11.130+0.229X1+0.290X2. The correlation value is 0.751 (strong). The coefficient of determination value is 56.5%. Fcount value 38.256 > Ftable 4.00 with a significance level of 0.000 < 0.05.